The perceived professionalism and credibility of citizen journalism in Egypt - Ahmed, Mona Mohamed Naguib (AUC Knowledge Fountain, 2017)
After 25 January revolution and high penetration rate of Internet in Egypt, the media landscape and the circle of news production has been changed. News production is not any more in news agencies and media organization’ hands after the propagation of the social media, but it becomes in ordinary citizens’ hands. The Egyptian citizens are equipped with their mobile phones and Internet access, which enable them to capture the news instantly and disseminate it to the public online through different online platforms. A survey has been conducted on 350 Egyptians undergraduate and graduate students from different private and public universities in Cairo to examine the perceived credibility and the perceived professional roles of the citizen journalists’ content. However, it was found that the majority of Egyptian depends on Internet for information more than other mediums and they usually spend more than three hours online daily. The most of respondents seek citizen journalists’ content to gratify surveillance needs. The largest portion of the sample has a positive attitude toward citizen journalists’ content and they perceive it as significantly credible information. It was found that there are five major factors that affect the perceived credibility of citizen journalists’ content, which are age, gender of the respondents, the reliance on Internet of information, the pre-existing experience of producing online citizen-based news or content before, and seeking such content for surveillance. It was found also that the Egyptians are more likely to related citizen journalists with the mobilizer, civic, and adversary journalistic professional roles.